The Influence Of Knowledge Of Pulmonary Tuberculosis Patients On Compliance With Taking Anti-Tuberculosis Drugs - Siti Kemala Sari; Irma Yanti Rangkuti; Rizkia Annisa Umri; Kesuma Wardani (Program Studi Pendidikan Biologi, 2023)
Pulmonary tuberculosis (TB) is the second infectious disease in the world after Covid-19 and the thirteenth leading cause of death worldwide in 2021. Indonesia has the second highest number of TB patients in the world after India. TB can be cured with regular treatment for 6 months. Prolonged treatment can cause TB patients to become bored and lead to drug withdrawal, causing drug resistance problems. The better the patient's knowledge about TB disease, length of treatment, side effects and complications can influence the decision to encourage patients to adhere to their treatment. The success of Tuberculosis treatment is influenced by patient compliance in taking medication. The type of research used was observational analytic with a cross sectional approach to determine the relationship between knowledge and adherence to taking medication. . Respondents of this study were pulmonary TB patients at Tanjung Rejo Percut health center as many as 51 people. This study used a questionnaire in its implementation. The analysis test used is the gamma test. The results of the study showed a relationship between knowledge and compliance with taking antituberculosis drugs in pulmonary tuberculosis patients. (p value 0.023). The results of the study showed that the majority of male gender, productive age, the final category of treatment was complete (92.2%), namely cured (53.0%), not cured (39.2%) and incomplete (7.8%). The majority of patients' knowledge was 78.4% in the good category and the majority of TB patients' medication compliance was 64.7% in the high compliance category